Why Brand Manufacturers Should Take Loss Leading Seriously - Roman Inderst; Martin Obradovits (ZBW – Leibniz Information Centre for Economics, 2020)
Manufacturers frequently resist heavy discounting of their products by retailers, especially when they are used as so-called loss leaders. Since low prices should increase demand and manufacturers could simply refuse to fund deep price promotions, such resistance is puzzling at first sight. We explain this phenomenon in a model in which price promotions cause shoppers to potentially reassess the relative importance of quality and price, as they evaluate these attributes relative to a market-wide reference point. With deep discounting, quality can become relatively less important, eroding brand value and the bargaining position of brand manufacturers, hurting their profits and potentially even leading to a delisting of their products. Linking price promotions to increased one-stop shopping and more intense retail competition, our theory also contributes to the explanation of the rise of store brands.
Keywords: D11; D22; D43; L11; L15; 330; loss-leading; product positioning; price competition; price promotion